"Remoteness" and environmental conflicts: some insights from the political ecology and economic geography of copper. (7th January 2005) - Muradian, Roldan; Folchi, Mauricio; Martinez-Alier, Joan
This paper describes some historical features of the global economic geography of copper, and explores the conditions underpinning environmental conflicts in this sector, while showing some examples. We found that Europe and Japan are progressively more dependent on imports from developing countries to cover internal copper demand. In contrast, copper production in the USA has considerably increased during recent decades. During the 1990s, there was a boom of Latin American copper exports, led by Chile. We point out that population density, negotiation strategies, environmental performance, distribution of profits and the local notion of social rights are the major steering forces of environmental conflicts in the mining sector. We argue that the location of mines in isolated regions, stricter environmental policies and investments in updating environmental technologies have prevented the emergence of environmental conflicts during the Chilean copper boom.